Spatial variations in dietary organic matter sources modulate the size and condition of fish juveniles in temperate lagoon nursery sites. (5th January 2015) - Escalas, Arthur; Ferraton, Franck; Paillon, Christelle; Vidy, Guy; Carcaillet, Frédérique; Salen-Picard, Chantal; Le Loc'h, François; Richard, Pierre; Darnaude, Audrey Michèle
Abstract: Effective conservation of marine fish stocks involves understanding the impact, on population dynamics, of intra-specific variation in nursery habitats use at the juvenile stage. In some regions, an important part of the catching effort is concentrated on a small number of marine species that colonize coastal lagoons during their first year of life. To determine the intra-specific variation in lagoon use by these fish and their potential demographic consequences, we studied diet spatiotemporal variations in the group 0 juveniles of a highly exploited sparid, the gilthead seabream ( Sparus aurata L.), during their ∼6 months stay in a NW Mediterranean lagoon ( N  = 331, SL = 25–198 mm) and traced the origin of the organic matter in their food webs, at two lagoon sites with contrasted continental inputs. This showed that the origin (marine, lagoonal or continental) of the organic matter (OM) available in the water column and the sediment can vary substantially within the same lagoon, in line with local variations in the intensity of marine and continental inputs. The high trophic plasticity of S . aurata allows its juveniles to adapt to resulting differences in prey abundances at each site during their lagoon residency, thereby sustaining high growth irrespective of the area inhabited within the lagoon. However, continental POM incorporation by the juveniles through their diet (of 21–37% on average depending on the site) is proportional to its availability in the environment and could be responsible for the greater fish sizes (of 28 mm SL on average) and body weights (of 40.8 g on average) observed at the site under continental influence in the autumn, when the juveniles are ready to leave the lagoon. This suggests that continental inputs in particulate OM, when present, could significantly enhance fish growth within coastal lagoons, with important consequences on the local population dynamics of the fish species that use them as nurseries. As our results indicate that continental OM can represent up to 62% of the flesh of the juveniles originating from these ecosystems, particular care should be taken to preserve or improve the chemical quality of riverine inputs to coastal lagoons. Highlights: Variations in the diet of Sparus aurata juveniles are described in a shallow temperate lagoon. We also investigate the origin of the organic matter sustaining juvenile growth in this coastal nursery site. Continental organic matter incorporation through diet differed according to the sampling site. Both body size and condition were significantly higher in the site under the highest continental influence. The origin of the organic matter used for juvenile growth in coastal lagoons modulates individual fitness.